Overview of Complete Blood Test Results in D3 Medical Laboratory Technology Students of the Ministry of Health of East Kalimantan - Askur; Sresta Azahra; Fitri Nur Rica; Nurul Anggrieni (Afiyatun Journal of Health Sciences, 2025)
Background: Anemia is a global health problem that affects women of reproductive age. In Indonesia, the prevalence of anemia in women aged 15-49 years reaches 23.7%. Health students are at high risk of anemia due to lifestyle factors and academic stress. This study aims to analyze the complete picture of the results of the complete blood test in D3 Medical Laboratory Technology students. Methods: Descriptive research with a cross-sectional design was conducted on 31 students of D3 Medical Laboratory Technology of the Ministry of Health of East Kalimantan in 2025. Complete blood test using a hematology analyzer with the parameters of hemoglobin, erythrocytes, hematocrit, leukocytes, type, and platelets. The data were analyzed descriptively with the mean, standard deviation, and frequency distribution. Results: The average hemoglobin level was 13.01 ± 0.83 g/dL with a range of 11.1-14.6 g/dL. The prevalence of anemia (<12 g/dL) was 12.9% (n=4), all of which were categorized as mild anemia. Average erythrocytes 4.54 ± 0.34 million/μL, hematocrit 39.58 ± 2.90%, leukocytes 8144 ± 2066 cells/μL, and platelets 317613 ± 56493/μL. All parameters were within the normal range. Conclusion: The majority of female students (87.1%) have normal hemoglobin levels. The prevalence of mild anemia at 12.9% indicates the need for nutrition screening and education programs. Further research needs to integrate iron status biomarkers to confirm the etiology of anemia.